Factors associated with dental attendance among adolescents in Santiago, Chile - Baelum Vibeke; Lopez Rodrigo (BMC, 2007)
Abstract Background Dental treatment needs are commonly unmet among adolescents. It is therefore important to clarify the determinants of poor utilization of dental services among adolescents. Methods A total of 9,203 Chilean students aged 12-21 years provided information on dental visits, oral health related behavior, perceived oral health status, and socio-demographic determinants. School headmasters provided information on monthly tuition and annual fees. Based on the answers provided, three outcome variables were generated to reflect whether the respondent had visited the dentist during the past year or not; whether the last dental visit was due to symptoms; and whether the responded had ever been to a dentist. Aged adjusted multivariable logistic regression models were used to assess the influence of the covariates gender; oral health related behaviors (self-reported tooth brushing frequency & smoking habits); and measures of social position (annual education expenses; paternal income; and achieved parental education) on each outcome. Results Analyses showed that students who had not attended a dentist within the past year were more likely to be male (OR = 1.3); to report infrequent tooth brushing (OR = 1.3); to have a father without income (OR = 1.8); a mother with only primary school education (OR = 1.5); and were also more likely to report a poor oral health status (OR = 2.0), just as they were more likely to attend schools with lower tuition and fees (OR = 1.4). Students who consulted a dentist because of symptoms were more likely to have a father without income (OR = 1.4); to attend schools with low economic entry barriers (OR = 1.4); and they were more likely to report a poor oral health status (OR = 2.9). Students who had never visited a dentist were more likely to report infrequent tooth brushing (OR = 1.9) and to have lower socioeconomic positions independently of the indicator used. Conclusion The results demonstrate that socioeconomic and behavioral factors are independently associated with the frequency of and reasons for dental visits in this adolescent population and that self-perceived poor oral health status is strongly associated with infrequent dental visits and symptoms.